Synthesis, Characterization and Antioxidant Studies of Curcumin Derivatives - Revathi, R.; Arul Ananth, D.; Rameshkumar, A.; Sivasudha, T. (Asian Journal of Chemistry, 2015)
Three curcumin derivatives having modification in active methylene group (1, 3) and keto groups (2) were successfully synthesized and characterized by 1H NMR and FT-IR spectroscopic techniques. The substitution on the active methylene site of curcumin increases the antioxidant behaviour but it is decreased on modifications in the carbonyl group. The observed results suggest that the structural modifications will help in tuning the antioxidant behaviour of curcumin. While comparing compound 1 which have strong donating group than compound 3, the former shows higher scavenging activity. This implies the electron donating strength also plays an important role in determining the antioxidant activity. The observed results will aid in developing new curcumin derivatives for better antioxidant properties.